2019
DOI: 10.1093/ageing/afy192
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a falls prevention exercise programme on health-related quality of life in older home care recipients: a randomised controlled trial

Abstract: Background:Falls have serious consequences for quality of life (QOL) and contribute substantially to the global burden of disease. Home care is an important arena to address falls prevention and QOL, but this vulnerable group of older adults is underrepresented in health research. This study explores the effects of a falls prevention exercise programme on health-related quality of life (HRQOL), physical function and falls efficacy in older fallers receiving home care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(74 citation statements)
references
References 29 publications
0
63
2
4
Order By: Relevance
“…These conditions are in line with research (Mat et al, 2018) indicating that Otago training for six months caused no reduction in the symptoms of chronic diseases, such as osteoarthritis, affecting the elderly. These results differ from those of other studies (Bjerk et al, 2019) which reported that Otago training-based training programs can improve physical health but cause no significant increase in the mental health status.…”
Section: Discussioncontrasting
confidence: 99%
“…These conditions are in line with research (Mat et al, 2018) indicating that Otago training for six months caused no reduction in the symptoms of chronic diseases, such as osteoarthritis, affecting the elderly. These results differ from those of other studies (Bjerk et al, 2019) which reported that Otago training-based training programs can improve physical health but cause no significant increase in the mental health status.…”
Section: Discussioncontrasting
confidence: 99%
“…Only five studies evaluated health and well-being related outcomes (81)(82)(83)(84)(85). Studies tended to limit to measuring product usability and end-user satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Five Randomised Controlled Trials (RCTs) evaluated health or well-being outcomes(81)(82)(83)(84)(85). Outcome measures fell into four categories: Balance and falls, level of physical activity(including compliance)and physical function, Quality of Life (QOL) and mental health and clinical measures.…”
mentioning
confidence: 99%
“…They receive the most sensory impressions. Intense sensory experiences strengthen the transmission of impulses to the brain, integration of stimuli and improvement of neuronal processes [8,9,10].…”
Section: Training Methodsmentioning
confidence: 99%